Performance of Local Peking Duck (Anas platyrhynchos domestica) with Commercial Probiotics (Probac) at Different Levels - alfan setya winurdana; Salnan Irba Novaela Samur (JOSAR (Journal of Students Academic Research), 2023)
Peking duck is one of the superior ducks that breeders are interested in keeping. Maintaining broiler ducks often occurs with several obstacles including mortality, high feed conversion and target body weight couldn’t achieve. The use of probiotics generally gives a positive response on livestock performance. This study aims to determine the performance of local Peking ducks with the addition of commercial probiotics (Probac) with different levels. The study used an experimental method with a completely randomized design with 4 treatments and 5 replications. Experimental level with P0 (without probiotics), P1 (1g/kg feed probiotics), P2 (2g/kg feed probiotics), P3 (3kg/kg feed probiotics) The variables observed were body weight, feed conversion and mortality. The best results showed that the use of a commercial probiotic (Probac) with a P2 level (2g/kg feed) had an effect on body weight, but had no effect on feed conversion and mortality in local Peking ducks. It is recommended to use a commercial probiotic (Probac) at a dose of 2g/kg of feed to increase the performance of local Peking ducks